2021
DOI: 10.1111/jcmm.16894
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of melatonin via regulating lncRNA JPX‐Wnt/β‐catenin signalling pathway in human osteosarcoma cells

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 81 publications
(88 reference statements)
0
32
0
Order By: Relevance
“…MLT plays different roles in cancers such as restoring drug sensitivity, inducing apoptosis, and inhibiting cell growth and metastasis, therefore it is a hormone as well as a cell protector and can be utilized as a natural agent in OS treatment [26,27]. It is identified that melatonin inhibits the proliferation and invasion of osteosarcoma cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MLT plays different roles in cancers such as restoring drug sensitivity, inducing apoptosis, and inhibiting cell growth and metastasis, therefore it is a hormone as well as a cell protector and can be utilized as a natural agent in OS treatment [26,27]. It is identified that melatonin inhibits the proliferation and invasion of osteosarcoma cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is identified that melatonin inhibits the proliferation and invasion of osteosarcoma cells in a dose-dependent manner. It also inhibits VEGFA and angiogenesis by targeting miR-424-5p [26,28]. ▶Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Assay. An in vitro scratch wound assay was used to evaluate cell migration [17]. KFs were seeded in 6-well plates at a density of 2 × 10 5 cells per well and incubated overnight (37 °C, 5% CO 2 ).…”
Section: Cell Migrationmentioning
confidence: 99%
“…TCGA has now emerged as an efficient and promising tool for elucidating gene-level alterations in 33 solid tumors by generating comprehensive data consisting of the epigenome, transcriptome, and proteome, as well as histopathology and various standard clinical parameters ( 89 ). The resultant resources allow us to comprehensively analyze the impact of MAGs on the clinical prognosis of LGG, the molecular mechanisms affecting prognosis, and the construction of further clinical prediction models.…”
Section: Discussionmentioning
confidence: 99%